if a x b = c x d and a x c= b x d, then prove that

Asked by  | 20th Feb, 2009, 05:19: PM

Expert Answer:

                  ax b = c x d ...(1)

                a x c= b x d...(2)

subtracting (1) from(2),

a x (b-c) =( c-b) x d

a x (b-c) +( b-c) x d=0

a x (b-c) - d x ( b-c) =0

(a-d) x (b-c)=0

Hence,|a-d|=0 or |b-c|=0
or (a-d) is parallel to (b-c).

Answered by  | 22nd Feb, 2009, 02:00: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.